Treatment of peri-implant soft tissue defects: A narrative review - Frizzera, Fausto; De Oliveira, Guilherme José Pimentel Lopes; Shibli, Jamil Awad; De Moraes, Kely Cristina; Marcantonio, Eloísa Boeck; Marcantonio, Elcio [UNESP] (FapUNIFESP (SciELO), 2019)
Soft tissue defects around dental implants, such as papilla or volume loss, peri-implant recession and alterations of the ridge color and/or texture, lead to esthetic and functional complaints. Treatments of these defects in implants are more demanding than in teeth because peri-implant tissue exhibits different anatomical and histological characteristics. This narrative review discusses the proposed treatments for soft tissue defects around implants in the current literature. Several clinical and pre-clinical studies addressed methods to augment the quantity of the peri-implant keratinized mucosa. Autogenous grafts performed better than soft tissue substitutes in the treatment of soft tissue defects, but there is no clinical consensus on the more appropriate donor area for connective tissue grafts. Treatment for facial volume loss, alterations on the mucosa color or texture and shallow peri-implant recessions are more predictable than deep recessions and sites that present loss of papilla. Correction of peri-implant soft tissue defects may be challenging, especially in areas that exhibit larger defects and interproximal loss. Therefore, the regeneration of soft and hard tissues during implant treatment is important to prevent the occurrence of these alterations.
Keywords: Dental implants; Esthetics; Soft tissue; Therapy; Transplants